English Linguistics Terms Based on Android Application (Terminoghraphy for English and Literature Students) - Hasrullah (Hasanuddin University, 2023)
This research discussed about Applied Linguistics in Termontography theory by Temmerman (2013). This research discussed about Applied Linguistics in Termontography theory by Temmerman 2013. This objective of the research are 1) to find out English and Literature students’ challenges in learning linguistics terminologies, and 2) to reveal the effectiveness of ELITE (English Linguistics Terminology), an Android application developed by the researcher, in addressing English and Literature students’ needs in learning linguistics terminologies at the English and Literature Department. The theory divided into five principles in making a specialized dictionary, in this case is Linguistics terminology. This research used corpus collection instrument by collecting data from several references. The finding showed that the Linguistics application was build based on the five principles of Termontography; (1) Monolingual, it uses English language as the user target for English literature students; (2) Structure Consecutively, there are 711 corpus collection words in linguistics terminology, they are set consecutively from A to Z initials; (3) Standard Description, corpus collection based on the Linguistics dictionary book of Cambridge university press 2013; (4) One design, the application provides a term and its definition; (5) Permanently; each term and its definition as well as the application are permanent used for Android user. Based on the result, the application could prove the theory of Temmerman about Terminography in its five principles, and it can be implemented to English Literature students.